2009
DOI: 10.1097/prs.0b013e3181bf803d
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermis–Assisted Prosthetic Breast Reconstruction versus Complete Submuscular Coverage: A Head-to-Head Comparison of Outcomes

Abstract: Acellular dermis allowed for a greater initial fill of saline. This potentially improves cosmetic outcome, as it better capitalizes on preserved mastectomy skin for reconstruction. The authors conclude that acellular dermis-assisted implant breast reconstruction has a safety profile no worse than that of complete submuscular coverage but offers the benefit of fewer expansions and the potential for more predictable secondary revisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
144
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(156 citation statements)
references
References 11 publications
2
144
1
2
Order By: Relevance
“…Certain questions surrounding HADM-assisted reconstruction have not yet been definitively answered, particularly whether the use of HADM results in reduced postoperative pain, shorter hospital stays and reduced expander fill times compared with traditional techniques (119,120). A multicentre prospective cohort study evaluating HADM-assisted immediate expander-based breast reconstruction (121) reported an overall complication rate of 4.6% (three of 65 breasts). The multicentre Canadian trial (NCT00956384) (122) comparing HADM-assisted single-stage, 'directto-implant' reconstruction with conventional two-stage expander implant reconstruction is currently underway and should clarify the role of HADM in 'direct-to-implant' reconstructions, and will also examine the cost effectiveness of the procedure.…”
Section: What Is the Role Of Acellular Dermal Matrix In Implantmentioning
confidence: 99%
“…Certain questions surrounding HADM-assisted reconstruction have not yet been definitively answered, particularly whether the use of HADM results in reduced postoperative pain, shorter hospital stays and reduced expander fill times compared with traditional techniques (119,120). A multicentre prospective cohort study evaluating HADM-assisted immediate expander-based breast reconstruction (121) reported an overall complication rate of 4.6% (three of 65 breasts). The multicentre Canadian trial (NCT00956384) (122) comparing HADM-assisted single-stage, 'directto-implant' reconstruction with conventional two-stage expander implant reconstruction is currently underway and should clarify the role of HADM in 'direct-to-implant' reconstructions, and will also examine the cost effectiveness of the procedure.…”
Section: What Is the Role Of Acellular Dermal Matrix In Implantmentioning
confidence: 99%
“…sion (Figs. [4][5][6]. In these cases, an inferior dermal flap was developed and used sutured to a superior sheet of ADM to provide full prepectoral implant coverage (Fig.…”
Section: Immediate Prepectoral Implant-based Reconstructionmentioning
confidence: 99%
“…5 These matrices can be made from human cadaveric skin or xenogenic materials such as porcine skin or bovine pericardium. Techniques have evolved from 2-stage complete submuscular placement of tissue expander (TE), 6,7 to single-stage direct to implant (DTI) reconstruction using partial submuscular coverage and an ADM to cover the lower part of the implant. [8][9][10] Excellent cosmetic outcomes can be achieved as the ADM facilitates natural ptosis and definition of the inframammary fold.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Because of its supreme biocompatibility as well as elastic and deformable properties, silicone has emerged as the material of choice. All prosthetic devices are hollow shells fabricated from a relatively tough silicone capsule filled with either saline or silicone gel.…”
Section: Prostheticmentioning
confidence: 99%
“…All prosthetic devices are hollow shells fabricated from a relatively tough silicone capsule filled with either saline or silicone gel. 6,16 Modern permanent implants come in a variety of sizes. They can be either smooth or textured, with some of the saline prostheses having the capability of postoperative size adjustment.…”
Section: Prostheticmentioning
confidence: 99%